Awareness towards roundtable on sustainable palm oil (RSPO) among independent smallholders / Adri Roslan - Roslan, Adri (Faculty of Plantation and Agrotechnology, 2016)
RSPO is an association that aims for the production of sustainable palm oil worldwide. The RSPO provides certification for oil palm stakeholders showing that they support the production of sustainable palm oil as well as proving that they obey the criteria of RSPO stating that also produce sustainable palm oil. This project is conducted to identify the factors that affect awareness towards RSPO among independent smallholders. This project was done by distributing questionnaires to random independent smallholders in Hulu Langat, Selangor. This project focuses on three factors that can affect awareness to RSPO. The factors are knowledge, attitude and interest. The effect of each of the factors on towards awareness of RSPO can be identified by using Pearson's Correlation and Multiple Linear Regression. Thus the most significant factor can be determined. From this project, knowledge is the most significant factor that affects the awareness towards RSPO among independent smallholders. Through regression analysis, knowledge shows highest coefficient reading 0.935. Whereas, the Pearson's Correlation also shows knowledge has the highest reading with 0.911 indicating that knowledge has a very strong relationship with awareness towards RSPO.